COMMUNITY INVOLVEMENT FOR SURABAYA’S PUBLIC TRANSPORT MANAGEMENT (Sinergi : Jurnal Ilmiah Ilmu Manajemen, 2019)
This paper will examine the correlation between theories and researches on community involvement with the planning for Surabaya’s public transport network. This departs from the idea of including affected community to join in the planning and designing process and one of the decision maker, rather than just a passive consumer, using researches related to participatory development on urban design practices. This paper will start from the idea of engaging communities in urban planning and development process to create a more resilient community and look for its examples in the city of Surabaya, Indonesia. Afterwards, this paper will observe the importance of effective and efficient transport management and the conditions of Surabaya's recent transit network and the efforts to improve it by implementing reports on rail-based transport. These two aspects, community involvement and provision of new public transport system then merged. The expected results are that the development of urban areas should be taking into account its surrounding neighbourhood, district, or corridor. In the end, this paper will generally recommend what steps should be taken, either for the transport management or the community involvement effort.